Paracoccidioidomycosis in an immunocompetent adult South of Minas Gerais: Case report (Research, Society and Development, 2022)
Paracoccidioidomycosis (PCM) is an infection that develops after inhalation of fungal parts dispersed in the atmosphere. It affects mainly males living in rural areas and since there is a higher incidence of the fungus in this environment. It presents several clinical manifestations, thus making the outcome of the diagnosis difficult. In this report, we describe the case of a 59-year-old man with a history of syncope followed by several generalized tonic-clonic seizures. After hospitalization and several complementary exams, the investigation culminated in the anatomopathological analysis of the transrectal resection of the prostate, investigating the presence of fungus, which resulted positive by PAS and Gragott staining for Paracoccidioides brasiliensis. The patient underwent treatment with Sulfamethoxazole 400 mg +Trimethoprim 80 mg, for two years, until clinical improvement and the results of requested complementary exams were obtained. The patient is under monitoring and has had no recurrences of the disease so far.